Ownership structure effect on relationship between information asymmetry and payment policy (Research, Society and Development, 2021)
Defining a shareholder payment policy depends on a corporate decision-making framework, or what may lead to conflicts of interest. In this context, the present study analyzes the moderating effect of ownership structure on the relationship between information asymmetry and payment policy of publicly traded Brazilian companies. The results do not reject the hypothesis (H1) that information asymmetry positively affects compensation when triggering. Regarding the moderating effect of ownership structure (H2), the results were not consensual, as ownership structure moderated the relationship between asymmetry and payment policy in only one of the two information asymmetry proxies. Thus, this research contributes to literature and stakeholders in the Brazilian stock market, presenting different perspectives, or moderating effect of ownership structure on the relationship between information asymmetry and shareholder valuation.